Effect of botanical drugs in improving symptoms of hypertensive nephropathy: Analysis of real-world data, retrospective cohort, network, and experimental assessment - Huan, Jia-Ming; Ma, Xi-Ting; Li, Si-Yi; Hu, Dong-Qing; Chen, Hao-Yu; Wang, Yi-Min; Su, Xiao-Yi; Su, Wen-Ge; Wang, Yi-Fei (Frontiers in Pharmacology, 2023)
Background/Aim: Hypertensive nephropathy (HN) is a common complication of hypertension. Traditional Chinese medicine has long been used in the clinical treatment of HN. However, botanical drug prescriptions have not been summarized. The purpose of this study is to develop a prescription for improving hypertensive nephropathy, explore the evidence related to clinical application of the prescription and verify its molecular mechanism of action. Methods: In this study, based on electronic medical record data on HN, the core botanical drugs and patients' symptoms were mined using hierarchical network extraction and fast unfolding algorithm, and the protein interaction network between botanical drugs and HN was established. The KNN model was used to analyze the clinical and biological characteristics of botanical drug compounds to determine the effective compounds. Hierarchical clustering was used to screen for effective botanical drugs. Clinical efficacy of botanical drugs was verified by retrospective cohort. Animal experiments were performed the target and pathway levels to analyze the mechanism. Results: A total of 14 botanical drug and 5 symptom communities were obtained from real-world clinical data, 76 effective compounds were obtained using the KNN model, and 7 botanical drugs were identified as Gao Shen Formula by hierarchical clustering. Compared with the classical model, the AUC value of the KNN model was the best; retrospective cohort verification showed that Gao Shen Formula reduced serum creatinine levels and CKD stage [OR=2.561, 95% CI (1.025-6.406), P < 0.05]. With respect to target and pathway enrichment, Gao Shen Formula acts on inflammatory factors such as TNF-α, IL-1β and IL-6 and regulates the NF-κB signaling pathway and downstream glucose and lipid metabolic pathways. Conclusion: In the retrospective cohort, we observed that clinical application of Gao Shen Formula alleviates the decrease in renal function in patients with hypertensive nephropathy. It is speculated that Gao Shen Formula acts by reducing inflammatory reactions, inhibiting renal damage caused by excessive activation of the renin-angiotensin-aldosterone system, and regulating energy metabolism.